2018
DOI: 10.1002/hep.29646
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of a healthy intestinal microbiota normalizes portal hypertension in a rat model of nonalcoholic steatohepatitis

Abstract: The IM exerts a direct influence in the development of PH in rats with diet-induced NASH and dysbiosis; PH, insulin resistance, and endothelial dysfunction revert when a healthy IM is restored. (Hepatology 2018;67:1485-1498).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 29 publications
5
93
0
1
Order By: Relevance
“…Metagenomic analysis found reduced abundance of Bacteroides and increased abundance of Firmicutes in the HFGFD group. Importantly, transplantation of gut microbiota from control to HFGFD animals restored insulin sensitivity, normalized endothelial dysfunction and reduced intrahepatic vascular resistance even as HFGFD feeding continued, although NAFLD histological scores remained unchanged . These findings indicate that the link between gut microbiota and PHT involves nonstructural (dynamic) components since the impact was independent of the presence and degree of liver fibrosis.…”
Section: Host‐microbiota Interactions and The Beginnings Of Portal Hymentioning
confidence: 79%
See 2 more Smart Citations
“…Metagenomic analysis found reduced abundance of Bacteroides and increased abundance of Firmicutes in the HFGFD group. Importantly, transplantation of gut microbiota from control to HFGFD animals restored insulin sensitivity, normalized endothelial dysfunction and reduced intrahepatic vascular resistance even as HFGFD feeding continued, although NAFLD histological scores remained unchanged . These findings indicate that the link between gut microbiota and PHT involves nonstructural (dynamic) components since the impact was independent of the presence and degree of liver fibrosis.…”
Section: Host‐microbiota Interactions and The Beginnings Of Portal Hymentioning
confidence: 79%
“…All animals receiving HFGFD developed steatohepatitis (steatosis, ballooning and lobular inflammation) with mild or absent fibrosis. Importantly, HFGFD was associated with significantly higher portal pressure compared to the control group and amounts of phosphorylated Akt and eNOS in the liver were reduced, consistent with insulin‐dependent endothelial dysfunction . Notably, faecal transplant derived from the HFGFD group was not sufficient to induce PHT in control animals.…”
Section: Host‐microbiota Interactions and The Beginnings Of Portal Hymentioning
confidence: 87%
See 1 more Smart Citation
“…García-Lezana et al (2018) showed that FMT restored a healthy intestinal microbiota and normalized portal hypertension in a rat model of NASH. Zhou et al (2017a) reported that FMT attenuated high-fat diet-induced NASH in mice via beneficial regulation of gut microbiota.…”
Section: The Microbiome As a Potential Therapeutic Target In Nafld Anmentioning
confidence: 97%
“…2 More recent studies suggest that the manipulation of the gut microbiome, either with antibiotics or FMT, also suppresses liver tumorigenesis and reduces portal hypertension in murine models. 3, 4 …”
mentioning
confidence: 99%